Lung cancer screening: the hidden public health emergency - Emily Stone; Rachael H Dodd; Henry Marshall; Billie Bonevski; Nicole M Rankin (Public Health Research & Practice, 2023)
Lung cancer causes nearly 2 million deaths per year worldwide, and cases continue to rise. Most lung cancer is diagnosed at late, incurable stages, and the five-year survival is a fraction of that for other common cancers, including breast, prostate, melanoma and colorectal cancer. Lung cancer screening (LCS) in high-risk populations using low-dose computed tomography (LDCT) could potentially save thousands of lives per year by shifting the stage at diagnosis to early curable disease. Although an LCS program has not yet started in Australia, two trials have provided local data on the feasibility, selection criteria and outcomes. A government-commissioned report has detailed a potential national program, and Federal Budget funding has been committed to early feasibility projects that include population-specific consultations with, for example, Aboriginal and Torres Strait Islander communities who are at higher risk of lung cancer due to high smoking rates. Effective recruitment to LCS, embedded smoking cessation and the provision of subsequent lung cancer care to all at-risk Australians remain key priorities for any future LCS program.